Influence of Employees' Empowerment, Engagement and Spouse Relations on Lecturers' Commitment in Southwest, Nigeria - ADEBIMPE, Abdulfatai Alabi; LASUN, Gbadamosi; Abosede , SUBUOLA, C. (International Journal of Educational Management, 2025)
Researches has shown that the achievement of educational objectives at the University level in Nigeria is strongly related to the commitment of the University lecturers. Thus, this study investigated the influence of employees' empowerment, engagement and spouse relations on university lecturers' commitment. The study adopted a survey research design of the expo facto type. A sample size of 1,382 married University academic staff and 108 Heads of Departments were selected using proportional and simple random sampling techniques. Five validated research instruments were used for data collection: Lecturers' Empowerment Scale (r= 0.755), Lecturers' Work Engagement Scale (r= 0.822), Lecturers' Attitude Towards Partners' Job Questionnaire (r=0.790) and Employee Commitment Survey Form (0.781). The hypotheses were tested using multiple regression analysis at .05 level of significance. The study revealed that there was a significant composite contribution of employees' empowerment, engagement and spouse relations to university lecturers' commitment (F 3, 1378 = 44.912; p < 0.05) and productivity (F 3, 1378 = 205.996; p < 0.05) in Southwest, Nigeria. Findings revealed no statistically significant moderating influence of gender on the contribution of employees' empowerment, engagement and spouse relations to commitment of university lecturers. Among others, the study recommended that university management should pay attention to improving lecturers' commitment by expanding lecturers' access to career development opportunities through participation in top management decision, improving working conditions and compensation system.